2015
DOI: 10.1161/strokeaha.115.009290
|View full text |Cite
|
Sign up to set email alerts
|

Microbleed Status and 3-Month Outcome After Intravenous Thrombolysis in 717 Patients With Acute Ischemic Stroke

Abstract: Although post-IVT sICH is an ominous event, a key clinical question remains whether the presence or burden of CMBs Background and Purpose-Whether cerebral microbleeds (CMBs) detected on pretreatment magnetic resonance imaging increase the risks of symptomatic intracranial hemorrhage (sICH) and, most importantly, poor outcome in patients treated by intravenous thrombolysis for acute ischemic stroke is still debated. We assessed the effect of CMB presence and burden on 3-month modified Rankin Scale and sICH in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1
3

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 31 publications
2
29
1
3
Order By: Relevance
“…8,17,[24][25][26][27] Individual patient data were not available from the BRASIL (Bleeding Risk Analysis in Stroke Imaging Before Thrombolysis) multicenter study (n=570) 28,29 with similar quality and characteristics to studies included. 7 We excluded 1 study of mainly intravenous and intra-arterial treatments.…”
Section: Resultsmentioning
confidence: 99%
“…8,17,[24][25][26][27] Individual patient data were not available from the BRASIL (Bleeding Risk Analysis in Stroke Imaging Before Thrombolysis) multicenter study (n=570) 28,29 with similar quality and characteristics to studies included. 7 We excluded 1 study of mainly intravenous and intra-arterial treatments.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, another metaanalysis showed that bleeding risk rises 1.9 times per CMH (47). However, it was shown that the risk did not rise in relation with the number of CMHs in some studies (42).…”
Section: Question: Can IV Tpa Be Administered To Patients With Cerebrmentioning
confidence: 91%
“…Balancing potential risks and benefits is required, but there is no measurement that can be used for this. CMH is found in 15-35% of patients in whom IV tPA will be administered, which means it is not rare (42). Having CMH causes 2.5 times more symptomatic intracerebral hemorrhage risk following IV tPA (43).…”
Section: Question: Can IV Tpa Be Administered To Patients With Cerebrmentioning
confidence: 99%
See 1 more Smart Citation
“…Cerebral microbleeds 44 and small-vessel disease 45 are also markers of increased risks for haemorrhagic transformation. However other studies have shown that this effect is modest and should not prevent the administration of rt-PA 46 . Theoretically, patients with pre-stroke cognitive impairment may have a higher sensitivity to the toxic effect of rt-PA and a lower capacity to recover from brain injury 47 .…”
Section: Intravenous Recombinant Tissue Plasminogen Activator (Rt-pa)mentioning
confidence: 94%